THE EARLY CHILDHOOD EDUCATOR: A CAREER OF CHOICE BEYOND THE 21ST CENTURY IN AFRICA - Chepsiror, Philomena Jepkemboi (Aulad : Journal on Early Childhood, 2020)
Sustainable Development Goal 8 calls for full, freely chosen and productive employment and decent work for all. However, Evidence from statistics shows that employment opportunities have continued to diminish world over and that the shortage of jobs is expected to continue in the near future. Africa bears the brunt for this unemployment situation. The good news however, is that early childhood education in Africa is growing in leaps and bounce and  is expected to continue growing as awareness around it intensifies. By making a critical analysis of pertinent literature, this paper sought to establish evidence to the fact that development in the early childhood education might be the magic bullet for the unemployment menace in Africa.  It was expected to inspire policy makers to step-up investment in early childhood education and mark it as a career of choice for the 21st century and beyond.